Strengthening Community Capacity Through Tsunami Education Programs in the Mangrove Community of Kebumen - Suwaryo, Putra Agina Widyaswara; Waladani, Barkah; Yuwono, Podo; Taufiqurrohman, Muhammad; Muzaki, Febilan Ahmad Fadhil; Hakimulfaiq, Mohammad Aziz (Universitas Nahdlatul Ulama Surabaya, 2024)
Coastal communities, such as the Mangrove Community of Kebumen, face significant risks from tsunamis due to their geographical location. This community service initiative aimed to enhance tsunami disaster preparedness through education and mangrove conservation. The objectives were to improve community knowledge on tsunami mitigation and to empower locals in mangrove planting and maintenance practices. The methodology involved a structured program conducted at Pantai Sawangan, Desa Puring, involving 30 participants from the mangrove community and local residents. The activities included pre-tests, educational sessions on tsunami mitigation and mangrove conservation, and post-tests to evaluate knowledge retention. Expert-led discussions highlighted the role of mangroves as natural barriers against tsunamis. Results showed a significant increase in participants' understanding of tsunami risks and mitigation strategies post-training. Participants actively engaged in practical sessions, demonstrating enhanced skills in mangrove planting and maintenance. Feedback indicated strong community support and a desire for continued educational initiatives. In conclusion, the program effectively improved community resilience through enhanced knowledge and practical skills in disaster preparedness and mangrove conservation. Continued socialization and educational programs are recommended to sustain community involvement and deepen understanding of disaster mitigation across diverse societal groups, ensuring long-term resilience against coastal hazards.